2013
DOI: 10.1159/000351521
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Viral Load by Quantitative Real-Time PCR in Herpes Simplex Encephalitis Patients

Abstract: Objective: Human herpesviruses cause various acute, subacute, and chronic disorders of the central nervous system and peripheral nervous systems in adults and children. The objective of the present study is to summarize the experience gained with the estimation of viral load in the central nervous system of children and adults with herpes simplex encephalitis (HSE) admitted to a neurological institute at Nagpur, India, by quantitative real-time PCR (qPCR) assay within the past 4 years. Methods: The qPCR assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
(21 reference statements)
1
17
1
1
Order By: Relevance
“…In support of this assumption, (i) we found no correlation between HSV PCR C T values, WBC counts, and protein levels, regardless of whether pooled or PCR assayspecific C T values were considered in the analysis. In line with this, the ranges of CSF WBC counts and protein levels were comparable between patients with confirmed CNS HSV infections displaying high (ÏŸ10,000 copies/ml) HSV DNA content in CSF and those with low content (Ïœ10,000 copies/ml), as determined by a quantitative real-time PCR assay (20). (ii) The overall median HSV PCR C T values were not significantly different between CSF specimens from patients that met the Reller criteria and those from patients that did not; nevertheless, the scant number of cases in the latter group limits the conclusions that can be made.…”
Section: Discussionsupporting
confidence: 78%
“…In support of this assumption, (i) we found no correlation between HSV PCR C T values, WBC counts, and protein levels, regardless of whether pooled or PCR assayspecific C T values were considered in the analysis. In line with this, the ranges of CSF WBC counts and protein levels were comparable between patients with confirmed CNS HSV infections displaying high (ÏŸ10,000 copies/ml) HSV DNA content in CSF and those with low content (Ïœ10,000 copies/ml), as determined by a quantitative real-time PCR assay (20). (ii) The overall median HSV PCR C T values were not significantly different between CSF specimens from patients that met the Reller criteria and those from patients that did not; nevertheless, the scant number of cases in the latter group limits the conclusions that can be made.…”
Section: Discussionsupporting
confidence: 78%
“…According to a Swedish report, 29 cases of acute HSV encephalitis were assayed by quantitative FQ-PCR. After analyzing the relationship between disease course and viral load, they found that the higher level of viral load in CSF, the graver disease severity and the longer disease course [10]. However, our study revealed no relevance between viral load and hospitalization duration.…”
Section: Discussioncontrasting
confidence: 74%
“…It is reported in the literature that the magnitude of viral load was closely correlated with disease severity [9]. And early diagnosis and early treatment could lower the viral load and boost the therapeutic efficacies [10]. In recent years, the arrival of fluorescence quantitative-polymerase chain reaction (FQ-PCR) has marked a great transformation from qualitative to quantitative analyses of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA was extracted from 200 ”l of CSF samples from patients by using a ZR viral DNA kit (Zymo Research, USA), according to the manufacturerÍŽs protocol. The amplification reactions were carried out using SYBR green and the primers for HSV which were described earlier (Bhullar et al, 2013). The cycle threshold (Ct) was calculated as the cycle number at which the …”
Section: Methodsmentioning
confidence: 99%